ASSESSING ACCOUNTABILITY OF PERFORMANCE MEASUREMENT SYSTEM AND LOCAL GOVERNMENT BUDGETARY MANAGEMENT - Mardiasmo Mardiasmo (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
Performance measurement system is an assessment tool, which assesses strategy implementation through financial and non-financial measures. Budget is one of the financial measures used to assess strategy implementation. It is a primary instrument of many function of decision, which is used as a tool to achieve organization goals. Public sector management has to fulfill vertical and horizontal accountability. To have a deeper understanding pertains to performance measurement system andlocal government budgetary management, this study assessed the existing performance measurement system and local government budgetary management in six municipal/districts. The result showed that the existing performance measurement system is an improper management tool, and that accountability of local government budgetary management is dominated by vertical accountability rather than horizontal accountability. It issuggested that each municipal/district should have its own revenue indica-tor and saving, increase its cost awareness and health and education sectordevelopment budget, implement New Public Management, and reform itsresponsibility system from vertical accountability to horizontal account-ability.